Novel Technique to Start DC Motor Using Wireless Power Transfer - Shubham Ananda Kale; Vitthal Sankpal; Lakhan Kharade; Pritam Powar (Journal of Power Electronics and Devices, 2017)
This paper represents the “Wireless start & control DC motor”. There is multiple needs and multiple uses for such technology. Our team chooses to research the feasibility of wireless power transmission through the inductive coupling. This wireless power transmission consists of using a transmission and receiving coil as the coupling coils. The first benefit to using this inductive coupling for simplicity of transmission & receiving antenna and second for small power transmission. This is much safer means of conveyance. To transfer power an alternating current should be passes through a closed loop coil. The primary coils alternating current will create a time varying magnetic field. The flux generated by this time varying magnetic field will then induced voltage on secondary coil. So the transmission distance is reduces then efficiency of any system using inductive coupling improve efficiency.